Evaluating Dutch Housing Market Regulation - Bas van der Klaauw; Udo Kock (Tinbergen Institute, 1999)
Although the primary goals of post war housing policy in The Netherlands have beenaccomplished, the Dutch housing market remains highly regulated. This paper develops a staticpartial equilibrium model to investigate the effects of deregulation on the private marketprices and the allocation of houses among households. We focus on three policy measures:individual rent support, social housing projects and the fiscal rules for owner occupiedhouses.
Keywords: 330; Wohnungspolitik; Wohnungsmarkt; Niederlande